Change management in information institutions - DukiÄ‡, Gordana; DukiÄ‡, Darko; Kozina, Goran (Malaysian Journal of Library and Information Science, 2017)
The purpose of this study is to examine how professionals employed in libraries, museums and archives assess changes and effectiveness of change management in their organisations. The intention is also to determine the underlying factor structure of the items representing their attitudes, and to explore the relationship between the perceived success in managing change and explanatory variables. This study involved a survey of 242 employees of Croatian information institutions. Descriptive statistics, factor analysis and ordinal logistic regression were employed to answer the research questions. The results show that respondents had a mildly positive attitude towards the changes that occurred in their institutions. They are largely aware of the importance and necessity of changes. However, the responses indicate that changes are not adequately managed. Three factors, which represent the underlying dimensions of the employees’ perceptions, were determined in the analysis. It was also found that the factors reflecting attitudes towards change management practice and impact of change positively influence the assessment of the institution's success in managing change, while employees’ awareness of the necessity of change, as well as gender, age, institution type and position in the management structure appear not to be strongly related to the outcome variable. Since only a few papers have examined the perception of change management by information professionals, the present study fills the gap in this area and contributes to a more comprehensive understanding of change management theory and practice.